Avaliação dos receptores e produção de citocinas em células natural killer (NK) obtidas do sangue periférico de pacientes com lesões neoplásicas tratadas com Interferon alfa-2b peguilado - ALVES, Eduardo Arthur Rodovalho (2016)
Seeking treatments to minimize invasive proceeding and reduce the risks related to premature birth or obstetrical problems, new therapeutic approaches have received great attention for the healing of cervical lesions in patients of reproductive age, and to propose new therapies, less invasive. The interferons are glycoproteins with immunomodulatory effect, antiviral, antiproliferative and antiangiogenic became widely used for this purpose. Many studies have demonstrated the antitumor effect of interferons, inducing effective immune responses. In an oncogenic virus infection of high-risk HPV, the immune system triggers multiple fighting mechanisms, however, modified cells by this virus can evade this response. Stimulate the immune system making it able to recognize these modified or infected cells has been a major challenge. Therefore, in this study, we assessed the role of natural killer cells against the systemic treatment with IFN-α 2b exogenous pegylated in patients with neoplastic lesions NICs II and III. We performed the analysis, by flow cytometry, of receptors NKT, NKG2D, KIRs, CD30, cytokines IFN-γ, IL-10, adhesion molecules CD50, CD54, CD102 and co-stimulatory CD80, CD86 responsive systemic treatment, in the peripheral blood of these patients. The groups general Pre-treated, 3rd, 6th Application were compared by 1 way ANOVA Friedman test and Dunn test's Multiple comparisons, and the groups Pre-treated, 3rd, 6th Application Good and Bad response were analyzed and compared by the median of the results using Mann-Whitney test for unpaired samples often significant considering the results of p lower than 0.05 (p <0.05). Our results were significant for the NKT receptors (p = 0.0263 / p= 0.0434), CD50 (p = 0.0205) and CD80 (p = 0.0205), and other markers did not show statistical significance among the groups. However concluded that poor systemic responsiveness to treatment may be associated with increased invariant NKT cells, adhesion molecules CD50 and co-stimulatory CD80, since patients who were poor response to immunotherapy showed a higher fluorescence intensity of these profiles at the beginning and third application treatment suggesting therefore that the functions of the immune system.